PREVENTION OF COVID-19 TRANSMISSION IN ISLAMIC BOARDING SCHOOLS (PESANTREN): LITERATURE REVIEW (Jurnal Mitra Kesehatan, 2021)
Introduction: COVID-19 is a disease caused by the SARS Cov 2 type corona virus with human-to-human transmission that causes respiratory tract infections, ranging from the common cold to serious diseases such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). Covid-19 has been designated as a global pandemic with a high risk of transmission in densely populated areas, one of which is Islamic Boarding Schools (Pesantren). The high social interaction of students in Islamic Boarding Schools causes students to be in a group at risk of being exposed to the corona virus. The purpose of this study is to find out the prevention of the transmission of Covid-19 in the Islamic Boarding Schools environment. Method: The writing methodology used is a literature review using various articles from Google Scholar, ScienceDirect, and ProQuest according to the inclusion and exclusion criteria of the journal that have been determined. Results: The results of this study are that Islamic boarding schools have attempted to prevent the transmission of Covid-19, including conducting health education related to preventing the transmission of Covid-19, providing hand washing facilities, conducting Tracing-Testing-Therapy (3T) for students with indications of Covid-19, providing self-isolation facilities, and implementing strict health protocols for all Islamic Boarding Schools residents. Conclusion: This research shows that Islamic boarding schools have attempted to prevent the transmission of Covid-19. The results of this study are expected to be a reference for related institutions to improve the quality of preventing the transmission of Covid-19 in the Islamic Boarding Schools environment.